Thermal behavior and microstructure evolution mechanism of W-20%Fe alloy fabricated by laser metal deposition. (1st October 2020) - Sun, Yixuan; Gu, Dongdong; Dai, Donghua; Guo, Meng; Ge, Qing; Shi, Xinyu; Li, Yanze; Le, Guomin; Yao, Mingxuan
Highlights: A three-dimension finite element model during LMD of W-20%Fe was established. Dimensions of the molten pool at different laser powers were discussed. Evolution of thermal behavior and melting/solidification process were studied. Solidification behavior and mechanisms of microstructure were concluded. Abstract: A three-dimensional finite element method (FEM) model was established to study the effects of laser processing parameters on the thermal behavior, melting/solidification mechanism, and microstructure evolution during laser melting deposition (LMD) of W-20%Fe alloy, considering the temperature-related thermal physical properties, multiple heat transfer, and latent heat of phase change. It was shown that there was a positive correlation between the maximum temperature and the laser powers. As the laser power increased, the cross-sectional configuration of the molten pool became deeper and narrower. The solidification characteristics, dependent on the solidification growth rate, R, and the temperature gradient, G, were obtained to predict the morphology and scale of the solidified microstructure. The maximum temperature gradient in the molten pool was slightly increased from 1.52×10 6 °C/m to 2.09×10 6 °C/m, as the laser power increased from 800 W to 1100 W. When the laser power was 1000 W and the scanning speed was 400 mm/min, the G / R elevated considerably from top to bottom region of the molten pool about 5.542°Cs/mm to 1829°Cs/mm. The columnar dendrites and the equiaxed dendrites were obtained at the bottom and top regions of the molten pool, respectively. The columnar dendrites were observed at the edge of the molten pool, which was attributed to the high G / R (2.09×10 9 °Cs/mm). The corresponding LMD experiment was carried out, which demonstrated that the established physical model was reliable and accurate. Graphical abstrat: Image, graphical abstract